Give Me Your Hands: Therapeutic Experiences of Collective Theatre Creation in Vancouver’s Downtown Eastside - Cook, Christopher; Borgen, William (Canadian Journal of Counselling and Psychotherapy, 2020)
In January 2016, a group of community members undertook a theatre project at the University of British Columbia’s Learning Exchange in Vancouver’s Downtown Eastside. For 22 months, group members wrote, rehearsed, and performed a collectively created script entitled Voices UP!. This research article casts four of the community members who took part in Voices UP! as co-inquirers, exploring their experiences of collective playmaking in terms of benefit to mental well-being. The article presents the study’s results in the form of a theatrical script, followed by a discussion that focuses on research outcomes relevant to therapists exploring creative art practices, including social connection through collaborative artmaking, puppetry as a unique theatrical tool for building therapeutic relationships and embodied expression, collective theatre creation and witnessing, and the unique challenges when terminating arts-based projects.